Prognostic significance of CD169‐positive lymph node sinus macrophages in patients with endometrial carcinoma. Issue 6 (3rd May 2016) - Ohnishi, Koji; Yamaguchi, Munekage; Erdenebaatar, Chimeddulam; Saito, Fumitaka; Tashiro, Hironori; Katabuchi, Hidetaka; Takeya, Motohiro; Komohara, Yoshihiro
Abstract : Lymph node (LN) macrophages play critical roles in anti‐tumor immunity, which develops via the activation of cytotoxic T cells (CTL) and NK cells. The present study aims to determine the prognostic significance of CD169 + LN macrophages in patients with endometrial carcinoma (EC). The number of CD169 + cells or the CD169 + ‐to‐CD68 + macrophage ratio in regional LN (RLN), and the number of CD8 + CTL or CD57 + NK cells in tumor tissues were investigated by immunohistochemistry in paraffin‐embedded tissue samples from 79 patients with EC. A high density of CD169 + cells in the RLN of patients with EC was correlated with an early clinical stage or no LN metastasis. A high number of CD169 + cells and a high CD169 + ‐to‐CD68 + macrophage ratio were significantly associated with longer overall survival in EC. We also found that the density of CD169 + macrophages was positively correlated with the number of CD8 + CTL and CD57 + NK cells that infiltrated into tumor tissues. A high density of CD57 + cells in EC tissues was associated with a better prognosis, while a high density of CD8 + cells was not linked to an altered prognosis. The present study showed that the density of CD169 + macrophages in RLN was associated with an improved prognosis in EC patients. CD169 + macrophages in RLN might represent a useful marker for assessing clinical prognoses and monitoring anti‐tumor immunity in patients with EC. Abstract : We have demonstrated the prognostic significance of CD169 + sinus macrophages in the RLNs of patients with EC. A greater number of CD169 + macrophages and an increased ratio of CD169 + ‐to‐CD68 + macrophages in the RLNs were significantly associated with a better clinical prognosis. CD169 + sinus macrophages found in RLNs may therefore be involved in cytotoxic T‐cell‐ and NK cell‐mediated antitumor immunity. Evaluation of CD169 protein expression in RLNs may aid estimations of clinical prognoses and improve the monitoring of anti‐tumor immune responses in patients with EC.